PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN PSYCHOLOGICAL EMPOWERMENT TERHADAP MINAT BERWIRAUSAHA - Tedi Kustandi; Sahara (Jurnal Witana, 2024)
The purpose of this research is to analyze the relationship between entrepreneurial education and psychological empowerment variables on the interest in entrepreneurship. We use a Quantitative approach in this research. The population in this study were 871 students of the Faculty of Economics, University of Muhammadiyah Cirebon, West Java. The sampling technique in this study used stratified techniques totaling 90 respondents. We used a questionnaire to collect sampling data. Using multiple linear regression analysis in data processing. The results showed that there was a positive and significant influence both partially and simultaneously between the variables of entrepreneurship education and psychological tempowerment on the interest in entrepreneurship.